Consentement libre et éclairé et les stérilisations imposées de femmes des Premières Nations et Inuit au Québec - Commission de la santé et des services sociaux des Premières Nations du Québec et du Labrador; Basile, Suzie; Bouchard, Patricia (2022)
La présente recherche vise à pallier le manque de données sur la stérilisation imposée de femmes des Premières Nations et Inuit au Québec. Il s’agit d’une occasion unique pour les femmes des Premières Nations et Inuit au Québec de faire connaître leur histoire et de témoigner dans un cadre respectueux des principes de recherche avec les peuples autochtones (Asselin et Basile, 2012). À notre connaissance, aucune étude n’a encore été menée sur le sujet au Québec, si bien que ce projet semble tout à fait inédit et permet de répondre à un réel besoin de faire avancer la recherche sur cette problématique. Dans cette intention, la recherche sur la stérilisation imposée des femmes des Premières Nations et Inuit permet de mettre en lumière les enjeux sous-jacents de cette problématique. Ainsi, la notion de consentement libre et éclairé est au coeur de la recherche, tout comme l’étude du racisme et de la discrimination systémique vécue par les femmes autochtones au sein du système de santé.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; intersectionnalité; justice reproductive; maternité; pol4102; premier cycle; périodes historiques; québec; recherche avec les peuples autochtones; régions géographiques; santé; sciences humaines; sciences sociales; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Genre, féminismes et développement: une trilogie en construction - Levy, Charmain; Martinez, Andrea (Collection "Études en développement international et mondialisation.", 2019)
Cet ouvrage pédagogique multidisciplinaire conçu pour les cours de premier cycle présente les principaux enjeux théoriques et pratiques de l'heure en matière de genre, féminismes et développement. Misant sur la capacité d'agir et le pouvoir de transformation sociale des femmes des Suds, ce livre examine les enjeux du genre et du développement. Ce manuel féministe, clair et facile à consulter, est spécifiquement conçu pour les cours de premier cycle universitaire sur les femmes, le genre et le développement international. Organisé en sept sections, il offre un panorama aussi vaste que possible des préoccupations féministes reliées au genre et au développement, alimentant ainsi les réflexions et les études de cas dans le domaine. Issu du colloque « État des lieux sur les perspectives féministes en développement international » du Congrès international des recherches féministes dans la francophonie (CIRFF), l'ouvrage propose des contributions de professeures-chercheuses et de militantes européennes, canadiennes et des Suds dédiées à l'avancement des connaissances féministes, à leur diffusion plus large et à leur vulgarisation. Publié en français
Keywords: afro-féminisme; approches et analyses; care; corps; cours; discipline; droits des femmes*; féminisme décolonial; féminisme postcolonial; histoire et politique; intersectionnalité; justice reproductive; outils; ouvrages de références; pol4022; premier cycle; ressource en ligne; santé; science politique; science politique et droit; thématiques; travail; violences; violences sexistes et sexuelles

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Vote, ovocytes et cosmétiques. Les trois jalons identitaires du recours au genre dans la recherche sur les cellules souches en Californie - Thompson, Charis; Sofio, Séverine (Cahiers du Genre, 2014)
Cet article explore les trois jalons identitaires du recours au genre [punctuated gendering] dans la recherche biomédicale sur les cellules souches en Californie. J’y défends l’idée selon laquelle le développement de ce secteur a eu besoin des femmes à trois reprises, mais pas de toutes les femmes à chaque fois. En d’autres termes, suivant les étapes que franchissait le développement de l’innovation autour des cellules souches, les femmes ont été sollicitées en fonction d’une perception du genre à chaque fois différente. Ainsi, il a d’abord fallu faire appel à elles en tant que citoyennes, au croisement des rapports de sexe, de race et de classe ; on a ensuite eu besoin d’elles en tant que corps biologiques ; elles ont, enfin, été sollicitées en tant que consommatrices. Le but de ce triple recours aux femmes selon des identités de genre à chaque fois spécifiques, fut d’abord d’attirer des capitaux publics et privés dans ce secteur, une fois le soutien de l’état californien garanti ; puis d’assurer l’approvisionnement de la recherche en morceaux de corps humain ; et enfin, de permettre le développement de l’économie autour de l’innovation sur les cellules souches. Cet article s’appuie sur mes précédents travaux sur la biomédicalisation et la marchandisation de la reproduction, mais il s’inscrit également dans la perspective des théories de la division sexuée du travail, et de la construction sociale du genre par la publicité et la consommation. Au croisement de ces logiques, l’innovation biomédicale apparaît donc comme un espace privilégié pour étudier le genre comme répertoire identitaire dynamique, à travers une mise en œuvre concrète de l’idée d’intersectionnalité.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; intersectionnalité; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

United in anger: a history of ACT UP - Hubbard, Jim; Schulman, Sarah; ACT UP Oral History Project; United in Anger, Inc (United in Anger, Inc., 2012)
"A unique feature-length documentary that combines startling archival footage that puts the audience on the ground with the activists and the remarkably insightful interviews from the ACT UP Oral History Project to explore ACT UP (the AIDS Coalition to Unleash Power) from a grassroots perspective - how a small group of men and women of all races and classes, came together to change the world and save each other's lives."
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; act up; amériques; approches et analyses; cinéma; communication; cours; discipline; documentaire; film; intersectionnalité; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; états-unis

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale - Larochelle, Émilie (2010)
Les femmes handicapées constituent un groupe de la population particulièrement vulnérable à la violence conjugale. En effet, elles risqueraient davantage que les autres femmes d’être victimes de violence de la part de leur conjoint et subiraient des formes plus sévères de violence (Brownridge 2006). Elles rapporteraient également de plus longues périodes d’abus (Nosek et autres 2001a). Pourtant, peu de ressources spécialisées en matière de violence conjugale leur sont accessibles, et les études sur l’accessibilité de ces ressources ainsi que sur la violence conjugale à l’égard des femmes handicapées se font rares. C’est dans ce contexte que l’Office des personnes handicapées du Québec (l’Office) et le ministère de la Santé et des Services sociaux (MSSS) se sont engagés à documenter la problématique de la violence conjugale envers les femmes handicapées dans le cadre du Plan d’action gouvernemental 2004-2009 en matière de violence conjugale (Québec 2004). Afin de remplir cet engagement, l’Office, en partenariat avec le MSSS, a entrepris en avril 2008 le projet intitulé Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale. Ce projet vise à : 1. Documenter la problématique de la violence conjugale envers les femmes handicapées. 2. Évaluer les besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale par le réseau de la santé et des services sociaux et les maisons d’hébergement. 3. Formuler des recommandations visant la prévention de la violence conjugale auprès des femmes handicapées ainsi que l’adaptation des services aux réalités particulières vécues par celles-ci. Ce projet d’évaluation, par ses résultats et ses recommandations, contribue également à répondre à l’une des priorités d’intervention de la politique gouvernementale À part entière : pour un véritable exercice du droit à l’égalité, soit agir contre toute forme d’exploitation, de violence et de maltraitance (Québec 2009 : 31). Rappelons que cette politique a été adoptée le 4 juin 2009 par le gouvernement du Québec et a pour but d’accroître, sur une période de dix ans, la participation sociale des personnes handicapées.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; amériques; approches et analyses; canada; care; cours; discipline; intersectionnalité; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; thématiques; travail social

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Les femmes autochtones au Canada : profil statistique d'après le recensement de 2006 - Affaires autochtones et développement du Nord Canada (2002)
Sommaire : points saillants de la situation des femmes autochtones au Canada. Structure de la population et lieu de résidence : •• En 2006, les femmes autochtones en Ontario représentaient environ 11 % de l’ensemble de la population d’identité autochtone. 31 % des femmes autochtones vivaient dans les provinces de l’Ouest (Manitoba, Saskatchewan, Alberta et Colombie‑Britannique). •• En 2006, l’âge médian de la population autochtone était de 27 ans, contre 40 ans pour la population non autochtone, une différence de 13 ans. Les résultats de l’étude révèlent que chez les Indiens inscrits vivant dans les réserves, un peu plus de femmes (44 %) que d’hommes (35 %) étaient âgés de 19 ans et moins. En comparaison, le pourcentage des Indiens inscrits vivant hors réserve âgés de 19 ans et moins était un peu plus élevé tant chez les femmes (45 %) que chez les hommes (43 %). De plus, de tous les groupes d’identité autochtone, c’est chez la population inuite féminine (49 %) et masculine (46 %) que se trouvait la proportion la plus importante des 19 ans et moins. •• La population féminine autochtone vieillit, quoique à un rythme plus lent que la population féminine non autochtone. En 2006, les femmes de 60 ans et plus représentaient plus de 7 % de l’ensemble de la population d’identité autochtone. Utilisation et connaissance des langues •• Les résultats de l’étude révèlent que la majorité des femmes autochtones, soit 73 %, ont appris l’anglais comme langue maternelle, tandis que seulement 16 % ont d’abord appris une langue autochtone et 8 %, le français. La proportion de filles et de femmes autochtones dont la langue maternelle est une langue autochtone (langue amérindienne ou inuktitut) est relativement faible dans les groupes d’âge plus jeunes, et plus élevée dans les groupes d’âge plus âgés. L’anglais prend donc plus d’importance que les langues autochtones et le français au fil du temps. •• La proportion de la population de langue maternelle autochtone est plus élevée chez les Inuites. Un plus grand nombre de femmes inuites de tous les groupes d’âge, soit 65 %, indiquent que l’inuktitut est leur langue maternelle, contre 32 % pour l’anglais. Chez 28 % des Indiennes inscrites, la langue maternelle est une langue autochtone; la proportion est beaucoup plus faible chez les Métisses, à 3 %. •• La vaste majorité (75 %) des Autochtones parlent principalement l’anglais à la maison, alors que 16 % parlent une langue autochtone et 5 %, le français. En outre, 29 % des membres des Premières nations affirment qu’ils peuvent parler une langue autochtone suffisamment bien pour tenir une conversation. La proportion est cependant beaucoup plus élevée chez les membres des Premières nations vivant dans les réserves. En 2006, la moitié des membres des Premières nations vivant dans les réserves (51 %) pouvaient s’exprimer dans une langue autochtone, contre 12 % de ceux qui vivaient hors réserve. Les langues des Premières nations les plus répandues en 2006 étaient le cri (87 285), l’ojibway (30 255), l’oji‑cri (12 435) et le montagnais‑naskapi (11 080).
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; démographie; famille; femmes* autochtones; géographie; histoire et politique; intersectionnalité; langue; langues autochtones; maternité; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; thématiques; transmissions; éducation; étude démographique

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

Not in our genes: biology, ideology, and human nature - Lewontin, Richard C.; Rose, Steven P. R.; Kamin, Leon J. (Pantheon Books, 1984)
Keywords: approches et analyses; biologie; corps; cours; discipline; génétique; intersectionnalité; justice sociale; lit4700; premier cycle; racisme; santé; sciences; sexisme; systèmes d'oppressions; thématiques

Avortement : un pays pas comme les autres - Harrison-Julien, Pasquale
L’avortement au Canada est une réalité complexe et souvent méconnue. De la Gaspésie au Nunavik, en passant par les provinces de l'Atlantique et les grandes villes, la série balado Avortement : un pays pas comme les autres met en lumière les disparités régionales et les obstacles rencontrés par les Canadiennes désirant avoir recours à ce soin de santé. La journaliste Pasquale Harrison-Julien aborde des sujets délicats tels que les avortements après le premier trimestre, les pressions culturelles et familiales, et les implications politiques et sociales des lois sur l'avortement. À travers des témoignages poignants et des entretiens avec des experts, des militants et des médecins, découvrez les histoires de femmes qui ont dû naviguer dans un système de santé inégal pour exercer leur droit dans ce balado essentiel pour comprendre les enjeux actuels et futurs de la santé reproductive au Canada.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; avortement; canada; communication; cours; discipline; droits des femmes*; intersectionnalité; journalisme; justice reproductive; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques

Contexte de vulnérabilité : femmes handicapées | INSPQ - Levasseur, Karine (Institut national de santé publique du Québec)
Keywords: EDI; amériques; approches et analyses; canada; capacitisme; care; cours; discipline; intersectionnalité; inégalités; justice sociale; premier cycle; québec; ressource en ligne; régions géographiques; santé; sex1920; sexisme; systèmes d'oppressions; thématiques